Powders for use in layer-by-layer deposition processes using lasers in the visible and near infrared range
By using core-shell structure powder particles in the SLS process, the near-infrared absorber is concentrated in the core part, and the problem of insufficient absorption capacity of the powder in the near-infrared range in the prior art is solved, achieving uniform melting of the powder and high density and uniformity of the piece.
Patent Information
- Application Number
- JP2024553879
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-15
- Filing Date
- 2023-03-15
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing SLS process, the powder has insufficient absorption capacity in the visible and near-infrared range, which makes it difficult for the laser to effectively bind the powder, resulting in uneven melting of the core part, causing partial melting and early solidification, which in turn causes deformation of the body.
Powder particles with a core-shell structure are adopted, in which the near-infrared absorber is concentrated in the core part, and the absorber is concentrated in the core through the precipitation step to form a core-shell structure to ensure uniform absorption of the powder in the near-infrared range.
The uniform melting of the powder in the near-infrared range is achieved, which reduces the possibility of deformation of the piece, improves the density and uniformity of the piece, and improves the dyeability and recyclability of the powder.
Smart Images

Figure 2025509448000001 
Figure 2025509448000002 
Figure 2025509448000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a powder for additive manufacturing, said powder comprising a composite particle containing a NIR absorbing component as a core particle, which allows homogeneous melting of the powder. [Background technology]
[0002] The powders typically used in SLS have poor absorption in the visible and near infrared ranges, and lasers that emit radiation in this wavelength range are difficult (if at all) to couple with the powders.
[0003] Powders are typically coated with absorbent pigments, usually in a dry blend process, where the absorbent pigments are primarily on the surface, resulting in low L of the powders so produced. * values arise. One alternative is to incorporate absorbent pigments into the polymer melt. The solidified melt is then granulated and subsequently milled. A disadvantage of the prior art is that the laser mainly couples with the surface of the powder particles. The core of the particle is therefore not melted directly by the laser, but only via thermal conduction from the strongly heated outer layer of the particle. As a result, the core of the particle is only partially melted, if at all, and acts as a crystallization seed, which causes premature solidification of the melt and a strong tendency to warp of the parts produced.
[0004] The rapid preparation of prototypes is a problem that has been much tackled in recent years. Particularly suitable are methods that operate on the basis of powdered materials and allow the desired structures to be produced layer by layer by selective melting and solidification. Support structures in the case of overhangs and undercuts can be omitted, since the powder bed surrounding the melted area provides sufficient support. Subsequent operations of removing the support are also avoided. The method is also suitable for small series production.
[0005] The selectivity of the layer-by-layer deposition can be brought about, for example, by the application of susceptors, absorbers, inhibitors, or via a mask, or via focused energy introduction, for example via a laser beam, or via glass fibers. Energy introduction is preferably achieved via electromagnetic radiation.
[0006] A particularly suitable method for rapid prototyping is selective laser sintering, in which a polymer powder is selectively irradiated for a short period of time with a laser beam in a chamber, melting the powder particles that are hit by the laser beam. The molten particles coalesce and rapidly resolidify to form a solid mass. By repeatedly irradiating successive newly applied layers, this method can be used to quickly and easily produce three-dimensional articles.
[0007] Laser sintering (rapid prototyping) methods for producing shaped articles from powdered polymers have been described extensively in US 6136948 and WO 96 / 06881. Many polymers and copolymers have been claimed for this application, such as polyacetate, polypropylene, polyethylene, ionomers and polyamides.
[0008] Other suitable methods are the SIV method as described in WO 01 / 38061 or the method as described in EP 1015214. Both methods work with flat infrared heating means to melt the powder. The selectivity of the melting is achieved in the former method by application of an inhibitor and in the latter method via a mask. Such a method is described in DE 103 11 438. In this method, the energy required for melting is introduced via a microwave generator and the selectivity is achieved by application of a susceptor.
[0009] Further suitable methods include those which work with absorbents which are present in a powder or which are applied by the inkjet method, as described in DE 10 2004 012 682.8, DE 10 2004 012 683.6 and DE 10 2004 012 683.7.
[0010] Said rapid prototyping or rapid manufacturing methods (RP or RM methods) can use powdered substrates, in particular polymers, preferably selected from polyester, polyvinyl chloride, polyacetal, polypropylene, polyethylene, polystyrene, polycarbonate, poly(N-methylmethacrylimide) (PMMI), polymethylmethacrylate (PMMA), ionomers, polyamides or mixtures thereof.
[0011] WO 95 / 11006 describes polymer powders suitable for laser sintering, which show no overlap of melting and recrystallization peaks while measuring their melting behavior by differential scanning calorimetry at scanning rates of 10° C. to 20° C. / min, a degree of crystallinity measured by DSC of 10% to 90%, and a number average molecular weight M n 30,000 to 500,000, and its M w / M n The ratio ranges from 1 to 5.
[0012] DE 197 47 309 describes the use of a copolyamide-12 powder with an increased melting temperature and increased enthalpy of fusion, which is obtained by reprecipitation of a polyamide previously prepared by ring-opening of laurolactam and subsequent polycondensation. This is polyamide-12.
[0013] WO 2007 / 051691 describes a method for producing ultrafine powders based on polyamides, in which a suspension containing inorganic particles suspended in an alcohol medium is used to produce powders with an average size dv of the inorganic particles in the range of 0.001 to 0.8 μm. 50 The method described comprises precipitating a polyamide in the presence of inorganic particles having the formula:
[0014] DE 10 2004 003 485 describes the use of particles with at least one cavity for use in a layer building method. All particles contain at least one cavity, and the particles containing the cavity are melted by the introduction of electromagnetic energy. The powder particles described have a surface layer of low thickness.
[0015] DE 102 27 224 describes granules for 3D binder printing, which consist of particles with a surface layer having a non-polar outer layer. However, the surface layer of the described powder particles has a small thickness.
[0016] In the prior art, the above powders are sometimes mixed with other particles, such as metal particles, glass particles, TiO2 particles, for reinforcement.
[0017] A variety of difficult to control characteristics of manufactured parts arise especially when powder handling is automated in rapid manufacturing. [Prior art documents] [Patent documents]
[0018] [Patent Document 1] U.S. Pat. No. 6,136,948 [Patent Document 2] International Publication No. 1996 / 06881 [Patent Document 3] International Publication No. 2001 / 38061 [Patent Document 4] European Patent No. 1015214 [Patent Document 5] DE 10311438 A1 [Patent Document 6] DE 102004012682.8 [Patent Document 7] DE 102004012683.6 [Patent Document 8] DE 102004020452.7 [Patent Document 9] International Publication No. 1995 / 11006 [Patent Document 10] German Patent No. 19747309 [Patent Document 11] International Publication No. 2007 / 051691 [Patent Document 12] German Patent No. 102004003485 [Patent Document 13] German Patent No. 10227224 Summary of the Invention [Problem to be solved by the invention]
[0019] The problem addressed by the present invention is therefore to provide a powder which exhibits good absorption in the near infrared range (NIR), and preferably also in the visible range, and which does not have the disadvantages of the prior art. [Means for solving the problem]
[0020] Surprisingly, it has been found that the above mentioned problem can be solved by a core-shell structure of the particles. The NIR absorber is concentrated in the core of the particle. This structure of the particles has the consequence that the powder particles are fused more homogeneously. The powder material is obtained by a precipitation process, where in the precipitation preferably at least 0.1% of the absorber is added so that the polymer surrounds this absorber and a shell-core structure is achieved.
[0021] The present invention therefore relates to a powder for use in a layer-by-layer deposition process for producing molded articles, in which regions of each powder layer are selectively melted by the introduction of electromagnetic energy, characterized in that the powder contains composite particles composed completely or partly of a core particle coated with a precipitated first polymer, said core particle containing a NIR-absorbing (near infrared-absorbing) component.
[0022] Near infrared (NIR) according to the present invention is in particular in the wavelength range of 780 to 1500 nm.
[0023] The NIR absorbing component may have an absorption of at least 40%, preferably 45%, more preferably 50%, particularly preferably 55% and very particularly preferably 60% at all wavelengths in the range 780-1500 nm. The term "all wavelengths" relates to all integer wavelengths.
[0024] The NIR absorbing component may have an absorption of at least 40%, preferably 45%, more preferably 50%, particularly preferably 55% and very particularly preferably 60% in the wavelength range of the electromagnetic energy of the laser from 780 to 1500 nm. The term "all wavelengths" relates to all integer wavelengths.
[0025] The NIR absorbing component may also have an absorption on average of at least 40%, preferably 45%, more preferably 50%, particularly preferably 55% and very particularly preferably 60% for wavelengths in the range of 780 to 1500 nm.
[0026] The NIR absorbing component should have an absorption of at least 40%, preferably 50%, more preferably 60%, particularly preferably 65%, and very particularly preferably 70% in the wavelength range of the electromagnetic energy of the laser (preferably ±10 nm). For example, the wavelength of the Nd-YAG laser is 1064 nm. For example, the wavelength of the laser of HPDL (high power diode laser) is 906 nm. However, high power diode lasers are available in several wavelengths and can be used according to the present invention. However, it is preferred if the high power diode laser emits radiation with a wavelength in the NIR range. Thus, the NIR absorbing component may have an absorption of at least 40%, preferably 50%, more preferably 60%, particularly preferably 65%, and very particularly preferably 70% in the wavelength of 906 nm (preferably ±10 nm) and / or 1064 nm (preferably ±10 nm). The specific laser or the wavelength of the laser is not limited in principle. However, a laser should be selected that is in the absorption range of the NIR absorbing component.
[0027] The absorption of NIR absorbing components can be determined from pure components (e.g. solids) using an integrating sphere. A detector in the integrating sphere is used to measure the transmitted radiation, which enters the integrating sphere through the sample. A reference measurement without a sample serves as a basis for calculations and to correct the results. A quartz glass cuvette can be used as the sample carrier. The cuvette consists of two halves of quartz glass, one of the halves has a cutout into which the powder can be poured. After filling, the halves are closed and uprighted to compress the powder bed. The thickness of the cutout is 0.2-0.5 mm (layer thickness). A suitable measuring instrument is the Agilent Cary UV-VIS-NIR 5000 instrument with a wavelength range of 250 nm to 2500 nm.
[0028] The NIR absorbing component may be a VIS absorbing component and a NIR absorbing component. Visible light (VIS) according to the present invention has a wavelength of 380 to 780 nm.
[0029] The NIR absorbing component should have an absorption of at least 40%, preferably 45%, more preferably 50%, particularly preferably 55%, and very particularly preferably 60% at all wavelengths in the range of 380 to 1500 nm. The NIR absorbing component and the VIS absorbing component may also have an absorption of at least 40%, preferably 50%, more preferably 60%, particularly preferably 65%, and very particularly preferably 70% in the wavelength range of the electromagnetic energy of the laser (preferably ±10 nm). Thus, the NIR absorbing component and the VIS absorbing component should have an absorption of at least 40%, preferably 50%, more preferably 60%, particularly preferably 65%, and very particularly preferably 70% at wavelengths of 906 nm (preferably ±10 nm) and 1064 nm (preferably ±10 nm).
[0030] The NIR and VIS absorbing components may have an absorption of at least 40%, preferably 45%, more preferably 50%, particularly preferably 55% and very particularly preferably 60% in the wavelength range of the electromagnetic energy of the laser from 780 to 1500 nm. The term "all wavelengths" relates to all integer wavelengths.
[0031] It is particularly preferred if the NIR absorbing component is an inorganic particle. The NIR absorbing component may comprise carbon black and / or TiO2. It is particularly preferred if the NIR absorbing component is carbon black. Carbon black absorbs not only in the NIR range but also in the VIS range, so that electromagnetic energy (or radiation) can be captured in the powder in a wider wavelength range. The NIR absorbing component should be insoluble during the precipitation process.
[0032] The NIR absorbing component may be the core particle, and in particular the core particle may be carbon black. It is also possible for the core particle to contain a mixture of carbon black and TiO2.
[0033] The NIR absorbing component has an L of 10 or less, preferably 5 or less, and particularly preferably 3 or less. * (CIEL * a *b * , in accordance with DIN EN ISO / CIE 11664-4). * The L value is a measure of the ability of a component to absorb electromagnetic energy (or radiation) in the NIR and / or VIS range. Carbon black meets the L * is a suitable component having a value.
[0034] The NIR absorbing component (especially carbon black) is ideally present in an amount of 0.01% to 7% by weight, preferably in an amount of 0.1% to 5% by weight, more preferably in an amount of 0.1% to 4% by weight, particularly preferably in an amount of 0.1% to 3% by weight, and very particularly preferably in an amount of 0.2% to 2% by weight, relative to the total weight of the composite particle. The core-shell structure of the composite particle according to the invention has the consequence that the proportion of the NIR absorbing component is essentially higher in the core of the composite particle than in the shell of the composite particle. The mass proportion of the NIR absorbing component in the core of the composite particle is preferably 10, 50 or 100 times higher relative to the total mass of the NIR absorbing components in the composite particle.
[0035] This is especially true for composite particles with high L * The individual NIR absorbing components have very low L * Even if the composite particle has a L value, * The composite particles have an L of more than 20, preferably more than 30, particularly preferably more than 50. * (CIEL * a * b * , in accordance with DIN EN ISO / CIE 11664-4).
[0036] The NIR absorbing component (especially carbon black) may be present in an amount of 1% to 100% by weight, preferably in an amount of 10% to 50% by weight, more preferably in an amount of 40% to 100% by weight, particularly preferably in an amount of 80% to 100% by weight, and very particularly preferably in an amount of 100% by weight, based on the total weight of the core particle. A value of 100% by weight, based on the total weight of the core particle, means that the core particle consists of the NIR absorbing component. However, it is possible that the core particle consists of the NIR absorbing component and a second polymer. The shell should ideally be free of the NIR absorbing component.
[0037] The layer-by-layer construction method for producing molded articles is preferably selective laser sintering.
[0038] Particular core particles may be configured in the following shapes: spherical, platelet or elongated. Furthermore, each core particle may have sharp, rounded or smooth ends. The core particles may be optionally coated with a size prior to application of the first polymer to be precipitated.
[0039] A precipitated / precipitable first polymer is a polymer that is soluble in a liquid medium containing a solvent and precipitated as a fully or partially insoluble precipitate in the form of flakes, droplets or in crystalline form through the modification of certain parameters, such as temperature, pressure, solvent, non-solvent, anti-solvent, precipitant content. The type of solvent and the solvent content, as well as further parameters for dissolving or precipitating the relevant polymer, are polymer dependent.
[0040] The precipitable / precipitated first polymer may be selected from polyolefins, polyethylene, polypropylene, polyvinyl chloride, polyacetal, polystyrene, polyimides, polysulfones, poly(N-methylmethacrylimide) (PMMI), polymethylmethacrylate (PMMA), polyvinylidene fluoride (PVDF), ionomers, polyetherketones, polyaryletherketones, polyamides, copolyamides, or mixtures thereof, in particular mixtures of homoamides and copolyamides. It is preferred if the precipitable / precipitated first polymer is a crystalline or semi-crystalline polymer. It is particularly preferred if the precipitable / precipitated first polymer is a polyamide or a copolyamide.
[0041] The precipitable / precipitated first polymer should be soluble in the precipitation step, in particular in the solvent used for precipitation. For example, the first polymer should be soluble in ethanol in the precipitation step. Soluble is understood to mean that in the precipitation step, for example at 145° C., at least 33 g / L (in particular 200 g / L) of the relevant polymer dissolves in the relevant solvent. The second polymer can be selected from polycarbonate, polymethylmethacrylate, polypropylene, polybutylene terephthalate, polyethylene terephthalate, polyetheretherketone, polyphthalamide or mixtures thereof. The core particles containing the second polymer are produced, for example, by grinding.
[0042] The second polymer should be insoluble in the precipitation step, in particular in the solvent used for precipitation. For example, the second polymer should be insoluble in ethanol in the precipitation step. Insoluble is understood to mean that in the precipitation step, for example at 145° C., not more than 10 g / L (particularly 1 g / L) of the relevant polymer dissolves in the relevant solvent.
[0043] The particles used for coating with the precipitated first polymer preferably contain a second polymer. In contrast to polymer powders that are only mixed (dry blended) with other particles or NIR absorbing components, the powders according to the invention no longer show demixing.
[0044] The powder according to the present invention preferably has a core-shell structure. The second polymer of the core particle can be any known polymer, provided that the second polymer is insoluble or essentially insoluble in the solvent in which the precipitated first polymer is dissolved. Thus, the second polymer is different from the (precipitated / precipitable) first polymer. The second polymer is different from the (precipitated / precipitable) first polymer at least in terms of its solubility properties in the specific solvent that dissolves the first polymer.
[0045] The precipitated first polymer for coating the core particles can be obtained by precipitation of at least one polyamide of AABB type or by co-precipitation of at least one polyamide of AB type with at least one polyamide of AABB type. Preference is given to co-precipitated polyamides in which at least polyamide 11 or polyamide 12 and at least one polyamide based on PA1010, PA1012, PA1212, PA613, PA106 or PA1013 are present.
[0046] For example, the following precipitable polymers may be mentioned: Polyolefins and polyethylenes are soluble, for example, in toluene, xylene or 1,2,4-trichlorobenzene. Polypropylene is soluble, for example, in toluene or xylene. Polyvinyl chloride is soluble, for example, in acetone. Polyacetals are soluble, for example, in DMF, DMAc and NMP. Polystyrene is soluble, for example, in toluene. Polyimides are soluble, for example, in NMP. Polysulfones are soluble, for example, in sulfolane. Poly(N-methylmethacrylimide) (PMMI) is soluble, for example, in DMAc or NMP. Polymethylmethacrylate (PMMA) is soluble, for example, in acetone. Polyvinylidene fluoride is soluble in N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAc) or cyclohexanone. Polyetherketones and polyaryleneketones are soluble in diphenylsulfone or sulfolane. Polyamides are soluble in alcoholic media, preferably a mixture of ethanol and water. As explained above, it may be necessary to adjust parameters such as temperature and pressure to dissolve certain polymers.
[0047] After dissolving a specific (first) polymer, it is precipitated in the presence of core particles, and these core particles are completely or partially coated with the specific precipitated first polymer. As mentioned above, a second polymer and / or NIR absorbing component that is insoluble or essentially insoluble under the conditions in which the first polymer is dissolved is selected as the core particle. The precipitation of the first polymer can be initiated / accelerated by changing the pressure, changing the temperature, changing (reducing) the concentration of the solvent, and optionally adding a non-solvent, anti-solvent or precipitant. Amorphous polymers, such as polystyrene, polysulfone, PMMI, PMMA, ionomers, require the addition of a non-solvent for the precipitation of the specific polymer.
[0048] The first polymer that can be precipitated is preferably a polyamide containing at least 8 carbon atoms per carbonamide group. It is particularly preferred if the polymer is a polyamide containing 10 or more carbon atoms per carbonamide group. It is very particularly preferred if the polymer is a polyamide selected from polyamide 612 (PA612), polyamide 11 (PA11) and polyamide 12 (PA12). The methods for producing polyamides that can be used in the sintered powder according to the invention are known, and the production of PA12 is described, for example, in DE 29 06 647, DE 35 10 687, DE 35 10 691 and DE 44 21 454. The required copolyamides are available from a variety of sources, for example polyamide 12 granules are available from Evonik Industries AG under the trade name VESTAMID.
[0049] It is particularly preferred if the precipitated / precipitable polymer is polyamide-12.
[0050] It is also possible to use corresponding copolyamides containing at least 70% by weight of said units, or mixtures of homopolyamides and copolyamides. As comonomers, they may thus contain from 0% to 30% by weight of one or more comonomers, such as caprolactam, hexamethylenediamine, 2-methylpentane-1,5-diamine, octamethylene-1,8-diamine, dodecamethylenediamine, isophoronediamine, trimethylhexamethylenediamine, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, aminoundecanoic acid. The abovementioned homopolyamides and copolyamides, referred to below as polyamides, are used as granules or pellets with a relative solution viscosity of 1.5 to 2.0, preferably 1.70 to 1.95 (measured at 25° C. in a 0.5% m-cresol solution according to DIN 53 727). They can be prepared by polycondensation, hydrolysis or acidolysis / activated anionic polymerization according to known methods. It is preferable to use balanced polyamides, having a ratio of NH2 / COOH end groups of 40 / 60 to 60 / 40. However, it is also advantageously possible to use unbalanced polyamides, preferably those having a ratio of NH2 / COOH end groups of 90:10 to 80:20, or 10:90 to 20:80.
[0051] The core particles have an average particle diameter dv of 1 μm or more. 50 In particular, the core particle has a size of 1 μm or more in all three spatial directions.
[0052] Furthermore, the core particles have an average particle diameter dv of 1 to 100 μm, preferably 10 to 80 μm, preferably 10 to 70 μm, more preferably 10 to 60 μm, more preferably 10 to 50 μm, and particularly preferably 10 to 40 μm. 50 may have:
[0053] Suitable particle size distribution can be ascertained via known methods, such as sieving, screening.
[0054] The composite particles have an average particle size dv of 20 to 150 μm, preferably 20 to 120 μm, preferably 20 to 100 μm, more preferably 25 to 80 μm, and particularly preferably 25 to 70 μm. 50 It is even more preferable if the compound has the following structure:
[0055] In preferred methods, the precipitated polymer coating has a thickness of 1.5 μm or more, more preferably 2, 3, 5, 10, 15, 20, 25, 30 μm or more.
[0056] The mass ratio of the polymer to the core particle with respect to the entire composite particle is preferably 0.1 to 30, preferably 1.0 to 20.0, and more preferably 1.3 to 10.0.
[0057] Average particle size of composite particles dv 50 , the average core diameter dv of the core particles 50 can be from 1.5 to 30, preferably from 1.5 to 25, more preferably from 1.5 to 15, even more preferably from 1.5 to 12, and particularly preferably from 1.5 to 10.
[0058] The powder according to the present invention has a particle size of 2 to 35 mm. 2 / g, preferably 2 to 15m 2 / g, particularly preferably 3 to 12 m 2 / g, and very particularly preferably 3 to 10 m 2 The powder according to the invention may further have a pour density PD in the range of 200 to 600 g / l, preferably in the range of 200 to 500 g / l.
[0059] The density of the core particles may be more or less than 20% lower than the density of the solvent used for precipitation of the first polymer, preferably less than 15%, more preferably less than 10%, and especially preferably less than 5%.
[0060] In the precipitation of the first polymer in the presence of the core particles, it is particularly preferred to use an alkanol (e.g. methanol, ethanol, propanol, butanol), preferably ethanol, as the solvent, whereby the density of the core particles is more or less than 20%, preferably less than 15%, more preferably less than 10%, and particularly preferably less than 5% lower than the density of the alkanol, preferably ethanol.
[0061] The powder may contain the composite particles alone or together with further fillers and / or auxiliaries incorporated in a free-flowing form (dry blend). The proportion of the composite particles in the powder is at least 50% by weight, preferably at least 80% by weight, preferably at least 90% by weight, particularly preferably at least 95% by weight, and very particularly preferably at least 99% by weight.
[0062] The powder according to the invention may further comprise auxiliaries and / or further organic or inorganic pigments. Such auxiliaries may for example be anticaking agents, such as precipitated and / or pyrogenic silica. Precipitated silica is commercially available in various specifications, for example under the trade name AEROSIL® by Evonik Industries AG. It is preferred if the powder according to the invention comprises less than 3% by weight, preferably 0.001% to 2% by weight, and very particularly preferably 0.025% to 1% by weight, of such auxiliaries, based on the total polymers present. The pigments may for example be titanium dioxide particles based on rutile (preferred) or anatase, or carbon black particles.
[0063] To improve the processability of the powder according to the invention or for further modification, said powder can be mixed with inorganic foreign pigments, such as transition metal oxides, stabilizers, such as phenols, especially sterically hindered phenols, flow control and anticaking aids, such as pyrogenic silica. The amounts in which these substances are added to the polymer, relative to the total mass of polymer in the polymer powder, are preferably such that the concentrations for the aids shown for the powder according to the invention are observed.
[0064] Optimal properties in the further processing of the powder are achieved if the melting point of the first polymer in the first heat is higher than in the second heat, as measured by differential scanning calorimetry (DSC), and if the melting enthalpy of the first polymer in the first heat is at least 50% higher than in the second heat, as measured by differential scanning calorimetry (DSC). The polymer of the shell of the composite particles (first polymer) has a high crystallinity compared to powders that can be produced by other methods through co-precipitation of the dissolved polymer with the particles. Polyamide 12, with a melting temperature of 185°C to 189°C, preferably 186°C to 188°C, a melting enthalpy of 112±17 kJ / mol, preferably 100 to 125 kJ / mol, and a solidification temperature of 138°C to 143°C, preferably 140°C to 142°C, is particularly suitable for sintering.
[0065] The invention also provides a method for producing a powder according to the invention, characterized in that the polymer is contacted in the presence of core particles with a medium containing a solvent capable of dissolving a first polymer at elevated pressure and / or temperature to produce an at least partial solution, and the first polymer is subsequently precipitated from said at least partial solution to obtain composite particles comprising a core particle fully or partially coated with the precipitated first polymer, said core particle containing a NIR absorbing component.
[0066] In a preferred method, the core particles (cores of the composite particles) have an average particle size dv of 1 μm or more, preferably 1 to 100 μm, preferably 10 to 80 μm, preferably 10 to 70 μm, more preferably 10 to 60 μm, more preferably 10 to 50 μm, and particularly preferably 10 to 40 μm. 50 Suitable particle size distribution can be ascertained via known methods, such as sieving, screening.
[0067] Of particular importance is the use of polymer core particles that are in suspension in a solvent for the precipitable first polymer. In a preferred process variant, the process of the invention uses a suspension of polymer core particles suspended in an alcohol medium, the core particles having the above-mentioned average particle size (dv 50 ) is a feature of this method.
[0068] The composite particles produced by the above-mentioned production method have an average particle size dv of preferably 20 to 150 μm, preferably 20 to 120 μm, preferably 20 to 100 μm, more preferably 25 to 80 μm, and particularly preferably 25 to 70 μm. 50 has.
[0069] It is an advantage of the process according to the invention that a step is omitted in the preparation of the polymer, since mixing in a dry blend of polymer particles and / or auxiliary / filler particles is no longer necessary.
[0070] Depending on their configuration, the core particles can be solid, hollow, or porous spheres. A particular core particle can be configured in the following shapes: spherical, platelet, or elongated. Furthermore, each core particle can have sharp, rounded, or smooth ends. The core particles can be optionally coated with a size prior to application of the precipitated first polymer.
[0071] The precipitable first polymer is preferably selected from polyolefins, polyethylene, polypropylene, polyvinyl chloride, polyacetal, polystyrene, polyimides, polysulfones, poly(N-methylmethacrylimide) (PMMI), polymethylmethacrylate (PMMA), polyvinylidene fluoride (PVDF), ionomers, polyetherketones, polyaryletherketones, polyamides, copolyamides, or mixtures thereof, in particular mixtures of homoamides and copolyamides.
[0072] The first polymer for coating the core particles can be obtained by precipitation of at least one polyamide of AABB type or by co-precipitation of at least one polyamide of AB type with at least one polyamide of AABB type. Preference is given to co-precipitated polyamides in which at least polyamide 11 or polyamide 12 and at least one polyamide based on PA1010, PA1012, PA1212 or PA1013 are present.
[0073] The type of solvent and the solvent content, as well as further parameters for dissolving and reprecipitating the relevant polymer, are polymer dependent and have already been explained above.
[0074] The following description relates to first polymers, particularly polyamides, which are soluble and precipitable in alcoholic media. To coat the core particles with polymers, other solvents are or must be used, the parameters and solvents must be adapted accordingly.
[0075] The method of the present invention preferably comprises subjecting the core particles to a medium containing a solvent capable of dissolving the precipitable first polymer, for example an alcoholic medium, at a temperature of 1000 kJ / m 3 The method is characterized by using a suspension obtained by suspending the core particles through the introduction of an energy input exceeding 1000 MPa. This generally results in a very useful suspension of the core particles in the medium. The specified energy input is achievable using known equipment. Suitable equipment includes planetary kneaders, rotor-stator machines, stirred ball mills, roller mills, etc.
[0076] The suspensions useful for the present invention are prepared in a medium containing a solvent capable of dissolving the precipitable first polymer, for example an alcoholic medium. In the case of an alcoholic medium, this may be a pure alcohol, a mixture of two or more alcohols, or water, or an alcohol with a content of other substances that do not essentially adversely affect the desired reprecipitation of the polyamide. The alcoholic medium of the suspension preferably has a content of non-alcoholic substances (preferably water) of less than 50% by weight, particularly preferably less than 30% by weight, and particularly advantageously less than 10% by weight of heterogeneous non-alcoholic substances. All types of alcohols or mixtures thereof that allow the reprecipitation of the polymer, preferably the polyamide, under the desired conditions (pressure and temperature) are generally suitable for the present invention. In the individual case, the skilled person is able to adapt the system to the specific requirements without much effort. The method of the present invention preferably uses one or more alcohols having a ratio of oxygen atoms to carbon atoms in the range of 1:1 to 1:5 as the alcoholic medium for the reprecipitation of the polyamide and / or the suspension of the core particles.
[0077] Typical alcohols for producing the suspension of core particles are those with an oxygen to carbon ratio of 1:1, 1:2, 1:3, 1:4 and 1:5, preferably those with an oxygen to carbon ratio of 1:2 and 1:3, particularly preferably those with an oxygen to carbon ratio of 1:2. It is very particularly advantageous to use ethanol in the production of the suspension of core particles and in the reprecipitation of the precipitable polymer, preferably polyamide.
[0078] As explained above, the precipitable first polymer is preferably selected from polyolefins, polyethylene, polypropylene, polyvinyl chloride, polyacetal, polystyrene, polyimides, polysulfones, poly(N-methylmethacrylimide) (PMMI), polymethylmethacrylate (PMMA), polyvinylidene fluoride (PVDF), ionomers, polyetherketones, polyaryletherketones, polyamides, copolyamides, or mixtures thereof, in particular mixtures of homoamides and copolyamides. The precipitable polyamide is dissolved in a suitable solvent and the core particles are coated on their surface by reprecipitation.
[0079] The reprecipitable polymer used is preferably a polyamide. The precipitable polymer is preferably a polyamide containing at least 8 carbon atoms per carbonamide group. It is particularly preferred when the polymer is a polyamide containing 10 or more carbon atoms per carbonamide group. Preferred polyamides that can be used as starting materials for the process of the invention include, inter alia, polyamide 11, polyamide 12, and polyamides having more than 12 aliphatically bonded carbon atoms per carbonamide group, preferably polyamide 11 or polyamide 12, preferably polyamide 12. It is also possible to use the corresponding copolyamides containing at least 70% by weight of the above units, or mixtures of homopolyamides and copolyamides. Thus, as comonomers, they may contain 0% to 30% by weight of one or more comonomers, such as caprolactam, hexamethylenediamine, 2-methylpentane-1,5-diamine, octamethylene-1,8-diamine, dodecamethylenediamine, isophoronediamine, trimethylhexamethylenediamine, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, aminoundecanoic acid. The abovementioned homopolyamides and copolyamides, hereinafter referred to as polyamides, are used as granules or pellets with a relative solution viscosity of 1.5 to 2.0, preferably 1.70 to 1.95 (measured at 25°C in a 0.5% m-cresol solution according to DIN 53 727). They may be prepared by polycondensation, hydrolysis or acidolysis / activated anionic polymerization according to known methods. It is preferable to use balanced polyamides with a ratio of NH2 / COOH end groups of 40 / 60 to 60 / 40. The polyamides used may contain up to 0.2% by weight of H3PO4. It is preferable to use H3PO4-free polyamides. However, it is also advantageously possible to use unbalanced polyamides, preferably those with a ratio of NH2 / COOH end groups of 90:10 to 80:20 or 10:90 to 20:80.
[0080] The solution of the precipitable first polymer, preferably polyamide, for reprecipitation can be prepared by all known methods. Ideally, a complete solution of the precipitable polymer, preferably polyamide, in the relevant medium, preferably alcoholic medium, in the presence of the core particles suspended therein is advantageous. The solution can be brought about by application of pressure and / or temperature. It is advantageous if the precipitable polymer, preferably polyamide, is initially charged in the alcoholic medium and dissolved by application of elevated temperature for the required time. The suspension of the core particles can be added before, during or after dissolution of the precipitable polymer, preferably polyamide. The suspension of the core particles is advantageously initially charged together with the precipitable polymer, preferably polyamide. The dissolution operation is advantageously assisted by the use of adapted stirring devices. The precipitation of the precipitable polymer, preferably polyamide, can also be assisted by application of pressure and / or temperature. Thus, for example, a reduction in temperature and / or distillative removal (preferably under reduced pressure) of the solvent, i.e. the alcoholic medium, preferably results in the precipitation of the precipitable polymer, preferably polyamide. However, it is also possible to aid the precipitation by adding an anti-solvent (precipitant).
[0081] After the formation of the composite particles, the method may further comprise post-treatment of the composite particles in a high shear mixer, the temperature being particularly preferably above the glass transition temperature of the particular polymer. These measures serve to round the particles and improve flowability.
[0082] The above parameters are specified as follows: The BET surface area was determined by determining the specific surface area after the BET method using a gas adsorption unit from Micromeritics in accordance with DIN ISO 9277 2003-05 (Micromeritics TriStar 3000 V6.03: V6.03 relates to the software version of the software Win3000). The BET surface area was determined by gas adsorption of nitrogen by the discontinuous volume method (DIN ISO 9277:2003-05, chapter 6.3.1). For this, multiple (7) measurement points are measured at relative pressures P / P0 between 0.05 and 0.20. The dead volume calibration was performed using He (with a purity of at least 4.6 [99.996%] according to the working instructions or at least 4.0 [99.99%] according to the standard, which also applies to N2). The samples were in each case degassed under vacuum for 1 h at room temperature (21 °C) and for 16 h at 80 °C. The specific surface area is based on degassed samples. The evaluation was carried out by multipoint measurements (DIN ISO 9277:2003-05, chapter 7.2). The temperature during the measurements was 77 K.
[0083] Particle size (fineness dv 50 ) was determined by laser diffraction. The measurements were carried out with a Malvern Mastersizer 2000. This is a dry measurement. For the measurements, a Scirocco dry dispersing device is used, in each case adding 20-40 g of powder. The vibrating conveyor chute was operated at 70% feed rate. The dispersion air pressure was 3 bar. For each measurement, a background measurement was performed (10 s / 10000 individual measurements). The measurement time of the sample was 5 s (5000 individual measurements). The refractive index and blue light value were determined to be 1.52. For the evaluation the Mie theory was used. The particle size distribution is a volume-weighted distribution.
[0084] The injection density is specified in accordance with DIN EN ISO 60.
[0085] The particle content is determined by ash / combustion residue determination according to DIN EN ISO 3451 Part 1 and Part 4.
[0086] Solution viscosity determination was performed according to ISO 307 in a 0.5% meta-cresol solution.
[0087] L * Value (CIEL * a * b * ) is determined in accordance with DIN EN ISO / CIE 11664-4 using an x-rite Color i7 spectrophotometer.
[0088] The invention also provides a method for producing molded articles by layer-by-layer build-up, in which selective areas of each powder layer are melted through the introduction of electromagnetic energy, where selectivity is achieved through the application of susceptors, inhibitors, absorbers or via a mask, where a powder according to the invention is used, in particular a powder containing composite particles which are core particles fully or partially coated with a precipitated polymer according to the invention, and where the wavelength of the electromagnetic energy is in the near infrared range, in the wavelength range 780-1500 nm.
[0089] The present invention also provides a molded article obtained from the powder according to the invention by the above-mentioned method. The molded article thus produced contains one or more polymers, preferably selected from polyolefins, polyethylene, polypropylene, polyvinyl chloride, polyacetal, polystyrene, polyimide, polysulfone, poly(N-methylmethacrylimide) (PMMI), polymethylmethacrylate (PMMA), polyvinylidene fluoride (PVDF), ionomers, polyetherketones, polyaryletherketones, polyamides, copolyamides, or mixtures thereof, in particular mixtures of homoamides and copolyamides. In a further embodiment, the polymer is at least one polyamide of AABB type, or a mixture of at least one polyamide of AB type and at least one polyamide of AABB type. Mixtures of polyamides are preferred, in which at least polyamide 11 or polyamide 12 and at least one polyamide based on PA1010, PA1012, PA1212, PA613, PA106 or PA1013 are present.
[0090] The advantages of this powder or method and / or of using the powder according to the invention are derived from the fact that the powder melts homogeneously and that a powder that is easy to dye is obtained, furthermore, the NIR absorbing components do not demix, less cavities form in the parts, better recyclability is achieved, the parts have a high density and a more homogeneous quality, a sharp separation between molten and non-molten areas is achieved and the parts show little warping.
[0091] The energy is introduced via electromagnetic radiation, and the selectivity is introduced, for example, via the application of masks, inhibitors, absorbers, susceptors, or through the concentration of radiation, for example, via a laser. It is particularly preferred when the selectivity of the layer-by-layer deposition process is achieved through the focused energy introduction. The electromagnetic radiation encompasses the range of 100 nm to 10 cm, preferably 380 nm to 10,600 nm, or 780 to 1500 nm. The radiation source may be, for example, a microwave generator, a suitable laser, a fiber laser, a heating laser or lamp, or a combination thereof. After cooling of all layers, the molded article can be removed.
[0092] The following examples of such methods are illustrative and are not intended to limit the invention.
[0093] The laser sintering method is well known and is based on selective sintering of polymer particles, where a layer of polymer particles is briefly exposed to laser light, so that the polymer particles exposed to the laser light bond to each other. By sintering layers of polymer particles one after the other, three-dimensional objects are produced. Details of the selective laser sintering method are described, for example, in US Pat. No. 6,136,948 (US 6,136,948) and WO 96 / 06881 (WO 96 / 06881).
[0094] Other suitable methods are the SIV method as described in WO 01 / 38061, or the method as described in EP 1015214. Both methods work with flat infrared heating means to melt the powder.
[0095] The selectivity of the melting is achieved in the former method by the application of an inhibitor and in the latter method via a mask. Such a method is described in DE 103 11 438. In this method, the energy required for melting is introduced via a microwave generator and the selectivity is achieved by the application of a susceptor.
[0096] Further suitable methods include those which work with absorbents which are present in a powder or which are applied by the inkjet method, as described in DE 10 2004 012 682.8, DE 10 2004 012 683.6 and DE 10 2004 020 452.7.
[0097] Molded articles produced by layer-by-layer deposition in which regions are selectively melted are characterized in that they contain at least one polymer and a polymeric toughening agent, and that the density of the composite part is reduced with respect to parts produced from composite powders according to the prior art. Furthermore, the tendency to warp is reduced and improved reproducibility of the mechanical properties of the molded article is achieved.
[0098] The molded article may further comprise auxiliaries (as previously mentioned for the polymer powders applies analogously), such as heat stabilizers, for example sterically hindered phenol derivatives. It is preferred if the molded article comprises less than 3% by weight, particularly preferably 0.001% to 2% by weight, and very particularly preferably 0.05% to 1% by weight, of such auxiliaries, based on the total polymer present.
[0099] Applications for these molded articles are evident in both rapid prototyping and rapid manufacturing. The latter particularly involves low volume production, i.e. the production of multiple identical parts, but which would not be economical to produce using injection molding. Examples include parts for premium passenger cars that are produced in small numbers only, or replacement parts for motor sports where not only are numbers low but availability time is also important. Industries in which the parts are used may include aerospace, medical engineering, mechanical engineering, automotive manufacturing, sports, home goods, electrical products and lifestyle.
[0100] The following examples illustrate the powders according to the invention and their uses, without however limiting the invention: The measurements of the pour density were carried out using an apparatus according to DIN EN ISO 60. EXAMPLES
[0101] Comparative Example 1: Reprecipitation of Nylon 12 (PA12) 348 kg of balanced PA12, produced by hydrolytic polymerization and having a relative solution viscosity of 1.62 and an end group content of 75 mmol / kg COOH or 69 mmol / kg NH2, was dissolved in 3 ml of ethanol modified with 2-butanone and having a water content of 1%. 3The mixture was brought to 145°C over 5 hours in a stirred tank (a=160 cm) and held at this temperature for 1 hour with stirring (blade stirrer, x=80 cm, speed=49 rpm). The jacket temperature was then reduced to 124°C and ethanol was continuously distilled off to bring the internal temperature to 125°C at the same stirring speed with a cooling rate of 25 K / h. From this point on, the jacket temperature was held 2 K-3 K below the internal temperature at the same cooling rate. The internal temperature was brought to 117°C at the same cooling rate and then held constant for 60 minutes. The distillative removal was continued with a cooling rate of 40 K / h to bring the internal temperature to 111°C. The onset of precipitation, detectable through the evolution of heat, occurs at this temperature. The distillation rate is increased so that the internal temperature does not exceed 111.3°C. After 25 minutes, the internal temperature drops, indicating the end of the precipitation. Through further distillative removal and cooling via the jacket, the temperature of the suspension is brought to 45° C. and the suspension is subsequently transferred to a paddle dryer. Ethanol is distilled off at 70° C. / 400 mbar and the residue is then subjected to further drying at 20 mbar / 86° C. for 3 hours.
[0102] Carbon black (Orion PRINTEX 60) is mixed by dry blending using a Henschel P10 mixer at 400 rpm for 5 minutes. This results in the powder summarized in Table 1.
[0103] [Table 1]
[0104] L * Value (CIEL * a * b * ) was carried out using an x-rite Color i7 spectrophotometer according to DIN EN ISO / CIE 11664-4.
[0105] Example 2: One-step reprecipitation of PA12 with core particles (invention).
[0106] The relative solution viscosity (η rel) 1.62 and PA12 with an end group content of 75 mmol / kg COOH or 66 mmol / kg NH2 was reprecipitated in the presence of 162.5 to 250 kg of particles having the characteristics shown in Table 2.
[0107] [Table 2]
[0108] In this example, the precipitation conditions were changed relative to Example 1 as follows: Precipitation temperature: 108℃ Settling time: 150 min Stirrer speed: 39~82rpm.
[0109] The properties (injection density, diameter and BET surface area) of the powder produced by Example 2 are summarized in Table 3. Table 3 also shows the amounts of polyamide, core particles and ethanol used, as well as the agitator speed used during the process.
[0110] [Table 3]
[0111] Example 2 according to the present invention shows that composite particles were produced in which carbon black (NIR and / or VIS absorbing component) was located inside the core. This was achieved by CIEL * a * b * L in color space * The carbon black to polymer ratio of the composite particles in Example 2 is the same as that in Comparative Example 1, but the L * The values are significantly higher. The carbon black is therefore located inside the composite, i.e. in the core of the particle. The NIR and / or VIS absorbing components inside the particle make it possible to ensure a homogeneous melting of the powder and thus reduce the tendency of warping of the parts produced. The high L of the composite particles * The value allows the powder / resulting molded article to be dyed.
Claims
1. A powder for use in a layer-by-layer process for producing molded articles, in which regions of each powder layer are selectively melted by the introduction of electromagnetic energy, the powder containing composite particles composed completely or partially of a core particle coated with a precipitated first polymer, the core particle containing a NIR absorbing (near infrared absorbing) component.
2. 2. The powder according to claim 1, characterized in that the NIR-absorbing component has an absorption of at least 40%, preferably 45%, more preferably 50%, particularly preferably 55% and very particularly preferably 60% at all wavelengths in the range from 780 to 1500 nm.
3. 3. Powder according to claim 1 or 2, characterized in that the NIR-absorbing component has an absorption of at least 40%, preferably 45%, more preferably 50%, particularly preferably 55% and very particularly preferably 60% at all wavelengths in the range from 380 to 1500 nm.
4. The NIR absorbing component is carbon black and / or TiO 2 4. Powder according to claim 1, characterized in that it comprises:
5. The NIR absorbing component has an L of 10 or less, preferably 5 or less, and particularly preferably 3 or less. * (CIE * a * b * , according to DIN EN ISO / CIE 11664-4) and / or The composite particles have an L * (CIE * a * b * 5. Powder according to claim 1, characterized in that it has a molecular weight of 1000 or more (in accordance with DIN EN ISO / CIE 11664-4).
6. 6. Powder according to claim 1 , characterised in that the NIR absorbing component is present in an amount of 0.01% to 7% by weight, preferably in an amount of 0.1% to 5% by weight, more preferably in an amount of 0.1% to 4% by weight, particularly preferably in an amount of 0.1% to 3% by weight, and very particularly preferably in an amount of 0.2% to 2% by weight, based on the total weight of the composite particle.
7. 7. Powder according to any one of claims 1 to 6, characterized in that the NIR absorbing component is present in an amount of 1% to 100% by weight, preferably in an amount of 10% to 50% by weight, more preferably in an amount of 40% to 100% by weight, particularly preferably in an amount of 80% to 100% by weight, and very particularly preferably in an amount of 100% by weight, based on the total weight of the core particle.
8. The core particles have an average particle size dv of 1 μm or more, preferably 1 to 100 μm, preferably 10 to 80 μm, preferably 10 to 70 μm, more preferably 10 to 60 μm, more preferably 10 to 50 μm, and particularly preferably 10 to 40 μm. 50 and / or The composite particles have an average particle size d 50 8. Powder according to claim 1, characterized in that it has
9. 9. The powder according to claim 1, characterized in that the core particle contains a second polymer, preferably the second polymer is different from the first polymer or the first polymer and the second polymer are the same polymer.
10. (A) the precipitated first polymer is selected from polyolefins, polyethylene, polypropylene, polyvinyl chloride, polyacetal, polystyrene, polyimide, polysulfone, poly(N-methylmethacrylimide) (PMMI), polymethylmethacrylate (PMMA), polyvinylidene fluoride (PVDF), ionomers, polyetherketones, polyaryletherketones, polyamides, copolyamides or mixtures thereof, in particular mixtures of homopolyamides and copolyamides, preferably polyamides, particularly preferably polyamide 11, polyamide 12 and polyamides having more than 12 aliphatically bonded carbon atoms per carbonamide group; and / or (B) the second polymer is selected from polycarbonate, polymethyl methacrylate, polypropylene, polybutylene terephthalate, polyethylene terephthalate, polyether ether ketone, polyphthalamide, or mixtures thereof; 10. Powder according to any one of claims 1 to 9, characterized in that it is
11. 11. Powder according to claim 1, characterized in that the proportion of composite particles in the powder is at least 50% by weight, preferably at least 80% by weight, preferably at least 90% by weight, particularly preferably at least 95% by weight and very particularly preferably at least 99% by weight.
12. 12. A method for producing a powder as defined in any one of claims 1 to 11, comprising contacting a polymer in the presence of core particles with a medium containing a solvent capable of dissolving a first polymer at elevated pressure and / or temperature to produce an at least partial solution, and subsequently precipitating the first polymer from said at least partial solution to obtain composite particles comprising core particles fully or partially coated with the precipitated first polymer, said core particles containing a NIR absorbing component.
13. 13. A method for producing moulded articles by a layer-by-layer build-up process, in which selective regions of the respective powder layers are melted through the introduction of electromagnetic energy, in which a powder according to any one of claims 1 to 11, in particular a powder containing composite particles which are core particles fully or partially coated with a precipitated polymer according to claim 12, is used, and the wavelength of the electromagnetic energy is in the near infrared range in the wavelength range 780-1500 nm.
14. 13. Use of a powder according to any one of claims 1 to 12 in a layer-by-layer building process for producing moulded articles, in which selective areas of the respective powder layers are melted through the introduction of electromagnetic energy, the wavelength of which is in the near infrared range, preferably achieving homogeneous melting of the powder and / or reducing the tendency of warping of the produced part.
15. Moulded article obtainable by the process according to claim 14, using a powder according to any one of claims 1 to 12.
Citation Information
Patent Citations
Polyamide powder and preparation method thereof
CN105694068A
Method for manufacturing three-dimensional titanium dioxide photocatalytic material from additive
CN109499561A
Powder for selective laser sintering, method for producing the powder, method for producing shaped article and shaped article produced by the method
JP2004137503A
Method for producing polyamide powder by precipitation
JP2020506991A
Process for producing a three-dimensional object
US20200140706A1